Rational optimization of a human neutralizing antibody of SARS-CoV-2. (August 2021) - Chen, Jiao; Wu, Fei; Lin, Dan; Kong, Weikang; Cai, Xueting; Yang, Jie; Sun, Xiaoyan; Cao, Peng
Abstract: SARS-CoV-2 has caused a worldwide epidemic of coronavirus disease 19 (COVID-19). Antibody drugs present an effective weapon for tens of millions of COVID-19 patients. Antibodies disrupting the interactions between the receptor-binding domain (RBD) of SARS-CoV-2 S protein and the angiotensin converting enzyme 2 (ACE2) effectively block SARS-CoV-2 cell entry into host cells. In order to rapidly develop more potent neutralizing antibodies, we utilized virtual scanning mutageneses and molecular dynamics simulations to optimize the antibody of P2B-2F6 isolated from single B cells of SARS-CoV-2 infected patients. Two potent P2B-2F6 mutants, namely H:V106R and H:V106R/H:P107Y, were found to possess higher binding affinities with the RBD domain of SARS-CoV-2 than others. Polar interactions are preferred near 106 and 107 paratope residues of the heavy chain. The mutations also increase the hydrogen-bonding network formed between the antibody and the RBD. Notably, the optimized antibodies possess potential neutralizing activity against the alarming SARS-CoV-2 variant of N501Y. This study provides insights into structure-based optimization of antibodies with higher affinity to the antigen. We hope that our proposed antibody mutants could contribute to the development of improved therapies against COVID-19. Highlights: SARS-CoV-2 spreads rapidly, threatening a global pandemic. This study optimized the antibody of P2B-2F6 isolated from single B cells of SARS-CoV-2 infected patients. Two P2B-2F6 mutants of H:V106R and H:V106R/H:P107Y were found to possess higher binding affinities with SARS-CoV-2 RBD. The optimized antibodies might have potential neutralizing activity against the alarming SARS-CoV-2 variant of N501Y.